2018
DOI: 10.3389/fmicb.2018.01743
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Genomic Features Characterize Two Clades of Corynebacterium diphtheriae: Proposal of Corynebacterium diphtheriae Subsp. diphtheriae Subsp. nov. and Corynebacterium diphtheriae Subsp. lausannense Subsp. nov.

Abstract: Corynebacterium diphtheriae is the etiological agent of diphtheria, a disease caused by the presence of the diphtheria toxin. However, an increasing number of records report non-toxigenic C. diphtheriae infections. Here, a C. diphtheriae strain was recovered from a patient with a past history of bronchiectasis who developed a severe tracheo-bronchitis with multiple whitish lesions of the distal trachea and the mainstem bronchi. Whole-genome sequencing (WGS), performed in parallel with PCR targeting the toxin g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 64 publications
4
19
0
Order By: Relevance
“…lausannense . Of interest, members of the newly described subspecies lausannense show a larger genome size and are enriched in genes related to transport and metabolism of lipids and inorganic ion (62). On the other hand, the new subspecies lacks all genes involved in the synthesis of pili, molybdenum cofactor, and nitrate reductase.…”
Section: Microbiology and Pathogenicity Of C Diphtheriaementioning
confidence: 99%
“…lausannense . Of interest, members of the newly described subspecies lausannense show a larger genome size and are enriched in genes related to transport and metabolism of lipids and inorganic ion (62). On the other hand, the new subspecies lacks all genes involved in the synthesis of pili, molybdenum cofactor, and nitrate reductase.…”
Section: Microbiology and Pathogenicity Of C Diphtheriaementioning
confidence: 99%
“…Hence, the five isolates were very closely related, showing that they belong to a single strain. In addition, this strain was phylogenetically distantly related (0.49% to 0.77% nucleotide p-distances) to all of the other C. belfantii isolates available in public repositories and from previous studies (16,21). One of the most closely related strains (separated from FRC0074 by a p-distance of 0.58%) was FRC0223, used as the outgroup in the SNP-based phylogeny of strains (Fig.…”
Section: Resultsmentioning
confidence: 70%
“…lausannense and C. belfantii was 99.3%. Besides, the former was positioned within the phylogenetic branch of C. belfantii ( Figure 1, S1 and S2 ), and the descriptions of both taxa are very similar (3, 13). Given that C. belfantii was validly published in October 2018, a few months before the taxonomic proposal C. diphtheriae subsp.…”
Section: Resultsmentioning
confidence: 85%
“…diphtheriae and C. diphtheriae subsp. lausannense (13). Here, we observed that the ANI value between the type strains of C. diphtheriae subsp.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation